2012
DOI: 10.1177/1059840512446069
|View full text |Cite
|
Sign up to set email alerts
|

Improving Immunization Coverage in a Rural School District in Pierce County, Washington

Abstract: Washington State has some of the highest percentages of school immunization exemptions in the country. We compared school immunization records in a rural school district in Pierce County, Washington, to immunization records in the state immunization information system (IIS) and parent-held records. Correcting school immunization records resulted in an increase in the number of students classified as fully immunized from 1,189 to 1,564 (p < .0001). We conducted school-based immunization clinics that increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
11
0
1
Order By: Relevance
“…They hold a unique position to promote and educate parents and school personnel about vaccinations. A study conducted in Washington State found parents were receptive to information about vaccinations provided by school nurses (Peterson et al, 2012). School nurses are in a position to clarify misconceptions and provide resources for parents about vaccinations (Luthy et.…”
Section: Discussionmentioning
confidence: 99%
“…They hold a unique position to promote and educate parents and school personnel about vaccinations. A study conducted in Washington State found parents were receptive to information about vaccinations provided by school nurses (Peterson et al, 2012). School nurses are in a position to clarify misconceptions and provide resources for parents about vaccinations (Luthy et.…”
Section: Discussionmentioning
confidence: 99%
“…Our study employs a quantitative research approach known as existing statistics analysis (Kendall, 2013;Neuman, 2011) in which we sampled existing individual-level data in the form of school attendance and influenza vaccination records (Davis, et al, 2008;Peterson et al, 2012) from a target population of 14,278 students in all 20 LISD elementary schools for school year (SY) 2011-2012. Attendance records were from LISD's databases, while vaccination records were from two sources: LISD and the City of Laredo Health Department.…”
Section: Research Design and Target Populationmentioning
confidence: 99%
“…69 • School nurses School nurses who are part of a school health program that is enrolled as a Vaccines ForChildren program provider play an integral role in achieving and maintaining high coverage of adolescent immunizations. 70 They can be valuable resources for delivering vaccines because of their knowledge of the school and its students, and access to immunization information systems may help increase their ability to provide vaccines to adolescent students. 71 However, school nurses also hold many responsibilities and may not have the time to participate in schoollocated vaccine programs because of competing job obligations.…”
Section: The School As An Alternative Vaccination Sitementioning
confidence: 99%